A lead-in safety study followed by a phase 2 clinical trial of dabrafenib, trametinib and hydroxychloroquine in advanced BRAFV600 mutant melanoma patients previously treated with BRAF-/MEK-inhibitors and immune checkpoint inhibitors. Issue 3 (29th March 2022) - Awada, Gil; Schwarze, Julia Katharina; Tijtgat, Jens; Fasolino, Giuseppe; Kruse, Vibeke; Neyns, Bart
Abstract : Patients with advanced BRAF V600 mutant melanoma who progressed on prior treatment with BRAF-/MEK-inhibitors and programmed cell death 1 or cytotoxic T-lymphocyte-associated antigen 4 immune checkpoint inhibitors can benefit from retreatment with the combination of a BRAF- and a MEK-inhibitor ('rechallenge'). Hydroxychloroquine can prevent autophagy-driven resistance and improve the efficacy of BRAF-/MEK-inhibitors in preclinical melanoma models. This clinical trial investigated the use of combined BRAF-/MEK-inhibition with dabrafenib and trametinib plus hydroxychloroquine in patients with advanced BRAF V600 mutant melanoma who previously progressed on prior treatment with BRAF-/MEK-inhibitors and immune checkpoint inhibitors. Following a safety lead-in phase, patients were randomized in the phase 2 part of the trial between upfront treatment with dabrafenib, trametinib and hydroxychloroquine (experimental arm), or dabrafenib and trametinib, with the possibility to add-on hydroxychloroquine at the time of documented tumor progression (contemporary control arm). Ten and four patients were recruited to the experimental and contemporary control arm, respectively. The objective response rate was 20.0% and the disease control rate was 50.0% in the experimental arm, whereas no responses were observed before or after adding hydroxychloroquine in the contemporary control arm. No new safety signals were observed for dabrafenib and trametinib. Hydroxychloroquine was suspected of causing an anxiety/psychotic disorder in one patient. Based on an early negative evaluation of the risk/benefit ratio for adding hydroxychloroquine to dabrafenib and trametinib when 'rechallenging' BRAF V600 mutant melanoma patients, recruitment to the trial was closed prematurely.